Barriers to the development of community-based nursing in Iran - Peyrovi, Hamid; Seyedfatemi, Naiemeh; Goharinezhad, Salime; Oghli, Saeid Hossein (Frontiers in Public Health, 2023)
Purpose Today, the care of chronic patients and older adult people in hospitals has moved towards community-based care, and health systems focus on disease prevention, health promotion, and rehabilitation. Community-based nurses play an essential role in early identification and intervention for these conditions. On the other hand, there is an increasing trend in ageing and chronic diseases in the world especially in Iran, which increases the importance of disease prevention and public health promotion. Therefore, the current research aims to identify barriers to the development of community-based nursing in Iran. Methods In this qualitative study, 12 semi-structured interviews were conducted with nursing experts recruited in the study by purposive sampling in 2021–2022. Interviews were recorded and transcribed and a framework analysis method was used to analyse the data. Results The results obtained from the analysis of documents and qualitative interviews led to the identification of 4 barriers: not having a specific position, inappropriate image of nursing in society, inadequacy of education with the needs of society, and high cost of home nursing services. Conclusion Improving the image of nursing in society, locating a special place in the health system, improving education, and adjusting the costs of home care could be the strategies that help the further development of community-based nursing (CBN).